Simplify the above square root as much as you can.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
1 0 + 4 6 + 1 0 − 4 6
= 4 + 4 6 + 6 + 4 − 4 6 + 6
= ( 2 + 6 ) 2 + ( 2 − 6 ) 2
= ( 2 + 6 ) 2 + ( 2 − 6 ) 2
= 2 + 6 + 2 − 6
= 2 + 2 = 4
The way to do these problems is to write the inside into a square, then cancel out the squares and the square roots to get a answer.